CORE CIVIL LAW ASPECTS OF EXTREME NECCESSITY (Law and world, 2017)
In modern conditions its is more and more necessary to widen guarantees for protection and implementation of civil rights. Protection of civil, i.e. private rights is possible either thorugh court, as well as by own effort in ocassions prescribed by law, that is without application to court. This is possible through using self-defence institute of the right. Self-defence of the civil rights is realted to the danger of infringement of such beneﬁ ts as life, health, personal dignity, freedom, assets, personal security. The objects of infringement are the rights and freedoms of person acring in self-defence, as well as legitimate iterests and rights of others, what gives grounds for application of self-defence. Self-defence of civil rights and freedoms is the comittment of actions of factual and/or legal nature by the person with his/her own effort, which aims to recover the infringed right and legitimate interest of a person, prevention and precluding of acts prohibited by the law in the framework of neccessary actions. The intititute of extreme neccessity must be developed. In this article the autthor substantiates the legality of imposition of damages on the person acting in conditions of extreme neccessity and the legal relations evolved in the extreme neccessiy are analysed. The essense of extreme neccessity is shown though comparison with adjacent institites.